Loan prospecting - Florian Heider; Roman Inderst (European Central Bank (ECB), 2012)
We offer a theoretical framework to analyze corporate lending when loan officers must be incentivized to prospect for loans and to transmit the soft information they obtain in that process. We explore how this multi-task agency problem shapes loan officers' compensation, banks' use of soft information in credit approval, and their lending standards. When competition intensifies, prospecting for loans becomes more important and banks' internal agency problem worsens. In response to more competition, banks lower lending standards, may choose to disregard soft and use only hard information in their credit approval, and in that case reduce loan officers to salespeople with steep, volume-based compensation. Our model generates "excessive lending" as banks' optimal response to an internal agency problem.
Keywords: D82; G21; L13; 330; banking; competition; loan officers; multi-task moral-hazard; soft information